Community Empowerment for Sustainable Geotourism in Sipinsur Geosite: Social and Economic Dimensions - Irma Ardianty Simanungkalit; Zulkifli Nasution; Erika Revida (TALENTA Publisher, Universitas Sumatera Utara, 2026)
This study examines how community participation can be strengthened in the development of geotourism at Sipinsur Geosite, located within the Toba Caldera Global Geopark, North Sumatra. Despite increasing tourist arrivals, local community involvement remains limited, largely confined to informal economic activities, and shows minimal participation in planning and decision-making processes. Using a qualitative approach, this research draws on semi-structured interviews, field observations, and focus group discussions involving local communities, government representatives, tourism managers, and visitors. The data were analyzed using thematic analysis to identify patterns of participation and key development challenges. The findings reveal that the main barriers to meaningful participation include limited access to training, inadequate infrastructure, weak stakeholder coordination, and the absence of structured mechanisms for community involvement. This results in a gap between tourism growth and local empowerment. This study highlights the need to shift from passive community involvement to a more inclusive, participatory governance model. Strengthening local capacity, improving collaboration among stakeholders, and integrating community voices into decision-making are essential to ensure more equitable and sustainable tourism development. By promoting a community-centered approach, Sipinsur Geosite can evolve into a more resilient destination that supports environmental conservation while enhancing local livelihoods.